2020
DOI: 10.1371/journal.pcbi.1007875
|View full text |Cite
|
Sign up to set email alerts
|

Randomly connected networks generate emergent selectivity and predict decoding properties of large populations of neurons

Abstract: Modern recording methods enable sampling of thousands of neurons during the performance of behavioral tasks, raising the question of how recorded activity relates to theoretical models. In the context of decision making, functional connectivity between choiceselective cortical neurons was recently reported. The straightforward interpretation of these data suggests the existence of selective pools of inhibitory and excitatory neurons. Computationally investigating an alternative mechanism for these experimental… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…The evolution of neuronal networks in vitro was characterized by coherent maturation of synaptic connectivity and ECM expression, partially resembling neuronal circuit development in vivo [14]. Synaptic connectivity of neuronal networks in vitro established randomly, mimicking the organization of cortical networks [3,61]. During cultivation, synapse density increased until maturity was reached after 21 days in vitro (DIV) (Fig.…”
Section: Cell Culturesmentioning
confidence: 89%
“…The evolution of neuronal networks in vitro was characterized by coherent maturation of synaptic connectivity and ECM expression, partially resembling neuronal circuit development in vivo [14]. Synaptic connectivity of neuronal networks in vitro established randomly, mimicking the organization of cortical networks [3,61]. During cultivation, synapse density increased until maturity was reached after 21 days in vitro (DIV) (Fig.…”
Section: Cell Culturesmentioning
confidence: 89%
“…they point to the same decision. We found that this task could be implemented by a unit-rank, single population network similar to perceptual decision-making (see also [Sederberg and Nemenman, 2020]), the only difference being that the two modalities correspond to two independent input patterns ( Supplementary Fig. S8).…”
Section: Implications For Structure In Neural Selectivitymentioning
confidence: 91%
“…In the mean-field model, we assume that choice selectivity of inhibitory neurons arises from specific connections from choice-selective excitatory neurons (Σ EI in our model). While it is possible that choice selectivity could arise from external inputs to interneurons 34 or even from random connections between excitatory and inhibitory neurons 35 , most circuit models assume stimulus information is exclusively provided by inputs to excitatory neurons. Inhibitory choice-selectivity also emerged in our RNNs trained to perform 2AFC task 25 .…”
Section: Discussionmentioning
confidence: 99%